Molecular Identification, Prevalence and Antimicrobial Susceptibility Profile of Salmonella enterica Isolated from Patients Attending Abubakar Tafawa Balewa University Teaching Hospital, Bauchi, Nigeria - Mohammed Aminu, Umar; Abubakar Muhammad, Zakkariya; Abba, Mustapha; Adamu, Aliyu; Auwal, Abdullahi; Yakubu, Adamu; Mustapha, Ibrahim; Ado Musa, Abuhuraira; Aliyu, Nurudeen; Muhammad, Bashir; Mohammed Abubakar, Bashir; Musa Moi, Ibrahim (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Salmonella enterica is a pathogenic bacterium associated with diverse clinical conditions such as gastroenteritis, diarrhea, and enteric fever. Its growing resistance to multiple antibiotics has been linked to numerous fatalities across the globe each year. Despite this public health concern, detailed data on the circulating serovars in Bauchi State remain scarce. This research was designed to explore the molecular identification, prevalence, and antimicrobial susceptibility profiles of Salmonella enterica isolated from patients at Abubakar Tafawa Balewa University Teaching Hospital, Bauchi,. In this cross-sectional study, 300 blood and stool samples were collected from patients showing symptoms of fever and gastrointestinal disorder at ATBUTH Bauchi between August 2023 and January 2024. Participants completed a self-administered questionnaire. Salmonella enterica was identified through culture, Gram staining, and biochemical tests, with confirmation via 16S rRNA amplification. The antimicrobial resistance pattern analysis was conducted with commercially prepared antibiotics using the Kirby-Bauer disk diffusion method. The prevalence of Salmonella enterica in blood and stool samples was found to be 4%. Salmonella typhi was the most frequently isolated pathogen, with 9 cases (75%), compared to Salmonella paratyphi, which accounted for 3 cases (25%). The highest occurrence was observed in the 0-10 age group at 1.70%, with no isolates detected in the 31-50 age range. Males had a slightly higher infection rate at 2.30% compared to 1.70% in females. The most effective antibiotics against Salmonella enterica included Amoxicillin-clavulanic acid, Gentamicin, Imipenem-cilastatin, Levofloxacin, Ceftriaxone-sulbactam, and Ofloxacin. In contrast, the highest resistance was noted with Cefuroxime, Ampiclox, Cefotaxime, Ceftazidime, Cefixime, Nalidixic Acid, and Nitrofurantoin. The results highlight the critical need for continuous monitoring and the implementation of focused antimicrobial interventions to manage Salmonella infections effectively.